Images of India in world literatures - Sil, Rita (New Delhi, India National Publishing House, 1987)
Contributed articles by Indian writers; most with reference to creative writings.
Includes bibliographical references and index.
Keywords: Literature, Modern -- History and criticism; India -- In literature